المسؤولية الاجتماعية تجاه العاملين و انعكاسها على اخلاقيات العمل : دراسة استطلاعية لآراء عينة من منتسبي بعض مستشفيات مدينة الموصل - د. ليث سعدالله حسين; ريم سعد الجميل (PROSPECTIVE RESEARCHES, 2023)
The Modern international challenges such as globalization has forced many Organizations towards reviewing and increasing their interests in the fields of Organizational education and human resources so as to be more responsive than before in the field of social performance. Thus, the social performance of the organization requires the achievement of some activities that are related to the objective of satisfying the social expectancy as well as its staff’s interest. The research deals with the relationship between the dimensions of social responsibility towards the employees and the work ethics within theoretic framework to embody fundamental concepts to the research dimension and the field framework to describe the research variables and to test its hypotheses. There were (48) questionnaires distributed among the individuals working in Mosul’s hospitals. For this purpose some statistical methods has been used to examine its hypotheses and variables. The research has come up with a result signifying that there is a correlation and effect between social responsibilities and work ethics for all employees (doctors and technicians). The research was ended by proposing some suggestions.